Morphology and Blue Photoluminescence Emission of PbMoO4 Processed in Conventional Hydrothermal - Sczancoski, J. C. [UNESP]; Bomio, M. D. R. [UNESP]; Cavalcante, L. S.; Joya, M. R.; Pizani, P. S.; Varela, José Arana [UNESP]; Longo, Elson [UNESP]; Li, M. Siu; Andres, J. A. (Amer Chemical Soc, 2009)
PbMoO4 micro-octahedrons were prepared by the coprecipitation method at room temperature without the presence of surfactants and processed in a conventional hydrothermal at different temperatures (from 60 to 120 degrees C) for 10 min. These micro-octahedrons were structurally characterized by X-ray diffraction (XRD) and micro-Raman (MR) spectroscopy, and its morphology was investigated by field-emission gun scanning electron microscopy (FEG-SEM). The optical properties were analyzed by ultraviolet-visible (UV-vis) absorption spectroscopy and photoluminescence (PL) measurements. XRD patterns and MR spectra confirmed that the PbMoO4 micro-octahedrons are characterized by a scheelite-type tetragonal structure. FEG-SEM micrographs points, out that these structures present a polydisperse particle size distribution in consequence of a predominant growth mechanism via aggregation of particles. In addition, it was observed that the hydrothermal conditions favored a spontaneous formation of micro-octahedrons interconnected along a common crystallographic orientation (oriented-attachment), resulting in self-organized structures. An intense blue PL emission at room temperature was observed in these micro-octahedrons when they were excited with a 350 nm wavelength. The origin of the PL emissions as well as its intensity variations are explained by means of a model based on both distorted [MoO4] and [PbO8] clusters into the lattice.